PROFIL PENALARAN MATEMATIS SISWA SMP DALAM PEMECAHAN MASALAH ARITMETIKA SOSIAL BERDASARKAN KEMAMPUAN MATEMATIKA - YULIANA DWI RAHMAWATI; Masriyah Masriyah (MATHEdunesa, 2021)
Mathematical reasoning is the ability to think about mathematical problems, namely by thinking logically about mathematical problems to get conclusions about problem solutions. There are several factors that can affect students' mathematical reasoning, including mathematical abilities. Dissimilarity of students' mathematical abilities allows for dissimilarity in their mathematical reasoning abilities. So, this research intends to describe students' mathematical reasoning abilities in solving social arithmetic problems based on dissimilarity in mathematical abilities. The purpose of this research was to describe qualitative data about the mathematical reasoning abilities of students with high, medium, or low abilities in solving social arithmetic problems. The instrument used was the Mathematical Ability Test to determine the three research subjects, followed by a Problem Solving Test to get qualitative data about students' mathematical reasoning abilities, then interviews to get deeper data that was not obtained through written tests. Thus, the research data were analyzed using mathematical reasoning indicators. From the result of data analysis, it was found that all students understood the problem well. Students with high and medium mathematical abilities are determining and implementing problem solving strategies properly, namely writing down the step for solving them correctly and making accurate conclusions by giving logical argumens at aech step of the solution. However, students with low mathematical abillities have difficulty in determining and implementing problem solving strategies because they do not understand the concept, thus writing the steps to solve the problems incorrectly and not giving accurate conclusions about the correctness of the solution. Keywords: mathematical reasoning, problem solving, mathematical abilities